Mediação e conciliação como instrumentos de governança na recuperação judicial - Cho, Tae Young (2017)
This thesis is prepared in the scope of law & economics in a microeconomic perspective to maintain the sources of economic activities, fomenting the national development in its all coverage aiming to analyze the Brazilian corporate governance policy and the jus economic model in practice for the recovery of the company in crisis, in the sense to suggest instruments to minimize and solve the conflicts arisen between stakeholders due to the adversarial system. The institute of the judicial recovery as a legal instrument to recover the company under crisis is a necessary condition, but not a sufficient one for having an appropriate environment in order to fulfill the LRE Law endeavor. The practice had shown that the sole negotiation of debts with creditors and its different classes do not have the divining to assure the success of the legal purposes of judicial recovery. The recovery plan is not equivalent to a sole installment payment or stretching the payment of the company’s debts. Therefore, it becomes necessary to pursue a corporate and administrative restructuring of the company under crisis as well as the use of instruments obtaining the collaboration between the stakeholders. By the same token, it is fundamental the involvement of the management bodies of the judicial recovery, the gatekeepers, with all the stakeholders, in order to align a governance policy in the judicial recovery to minimize or avoid potential conflicts among them